Scholarly publication key performance indicator diagnostic model using viable system and social cognitive theory - Bhathal Singh, Sharanjit Kaur (2016)
Scholarly Publications (SP) are almost certainly the most significant resources by which researchers at universities are appraised. It is part of the requirements for obtaining a Research University (RU) status. In the aspiration of these, to strategically improve and maintain their status, a series of performance measurement interventions were initiated, such as the use of Key Performance Indicators (KPI) delivery. The aim of this study is to propose a diagnostic model for SP productivity involving various stakeholders in monitoring a complex KPI delivery ecosystem for Malaysian university. This study employs Viable System Model (VSM) and Social Cognitive Theory (SCT) factors to develop a research model based on a comprehensive literature review. Following an interpretive paradigm this research applies qualitative method triangulated with quantitative method. VSM was applied as a diagnostic tool to diagnose process of KPI delivery for monitoring four recursion levels involving Deputy Vice Chancellor of Research and Innovation (DVCRI), Research Alliances (RAs), Research Groups (RGs) and lastly the academic staffs of the chosen institution which is, Universiti Teknologi Malaysia (UTM). Three strategies which are strategic, tactical and operational in achieving the SP KPI to maintain RU status for the institution were recommended to assist all pertinent stakeholders in monitoring the KPI delivery. Besides, to complement the results, a survey was designed and the data from the institutional repository involving UTM faculty members were analyzed to investigate the SCT factors involving human factor which is lacking in VSM tool. The findings show that the most influential factors for the SP of UTM are age, gender, experience, rank, teaching load, collaboration, funding, resource, discipline and skill. The model was evaluated for the SP KPI monitoring process, which further can be used by public and private universities to improve the performance of their institution's publication.